THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY TO FIRM VALUE WITH PROFITABILITY AND LEVERAGE AS A MODERATING VARIABLE ( STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2010-2012 ) - Putri Yuliana Mandasari; Kamaliah '; Rheny Afriana Hanif (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2013)
The aims of this research are to know ;1) the influence of corporate socialresponsibility (CSR) to firm value,and, 2) the influence of profitability andleverage as the moderating variables in relation between corporate socialresponsibility and firm value. The research sample is manufacturing sector inperiod 2010-2012 by using purposive sampling method. There are 37 companiesfulfilling criterion as this research sample. The research data was analyzed usingmoderated regression analysis with SPSS version 17.0.The results of this research showid that corporate social responsibility had apositive effect on firm value. For moderating proxies by return on asset andleverage proxies by debt to equity ratio were not a moderating variable inrelation between CSR and firm value.Keyword : Corporate Social Responsibility, Firm Value, Profitability, andLeverage.